Em nome do Laico, do Cisma, da Liberdade Religiosa, amém - Weber, Bruno Curtis (2022)
This paper discusses how religious freedom is being presented at the Brazilian Parliament. First, a short conceptual discussion on secularization and laicité is presented, assuming that both categories refer to religious transformations in modernity, although with different meanings: whereas secularization regards a “split” between State and religion, laicité refers to multiples religious participation perspectives on public sphere – atheist included. The latter has become a constitutional principle through the institution of freedom of believe. Second, a qualitative analysis of 72 draft bills on religious freedom issues in course on the Brazilian National Congress is presented. Data suggests that both categories – the separation between State and religion, and religious participation on public sphere – are set by representatives in the name of freedom of believe, but specifically on christian axiological perspective. Therefore, religious pluralism, a fundamental principle to constructing laicité and religious freedom, has been put into question by legislative practice.